The Support Hospital Opioid Use Disorder Treatment (SHOUT) Texas program implementation strategy for expanding treatment for hospitalized adults with opioid use disorder - Moriates, Christopher; Boulton, Alanna; Bottner, Richard; Weems, John; Christian, Nicholaus; Bazajou, Taylor; Olmos, Daniela I; Bolton, Carma Deem; Karns-Wright, Tara E; Lanham, Holly J; Finley, Erin P; Potter, Jennifer S (Journal of substance use and addiction treatment, 2025)
In 2017, we launched the "B-Team" (buprenorphine team), the first hospitalist-led opioid use disorder (OUD) treatment program in Texas. Based on initial success, we obtained funding from Texas Health & Human Services to expand the model to other hospitals in Texas through the Support Hospital Opioid Use Disorder Treatment (SHOUT) Texas program. This is a mixed methods study of the implementation of the SHOUT program, which is an OUD treatment intervention, in different hospitals in Texas. Our implementation approach combined training, tailoring, and technical assistance following the Replicating Effective Programs (REP) strategy with statewide telementoring delivered via Project ECHO. To evaluate the reach, adoption, and impact of SHOUT Texas, we assessed: 1) participating hospitals (adoption); 2) patients screened for OUD (impact); 3) patients started on medications for OUD (impact); 4) patients discharged with coordinated outpatient care (impact); 5) providers and staff trained via ECHO (reach); and 6) satisfaction with ECHO training (impact). Additionally, semi-structured interviews were conducted with key stakeholders at expansion sites to identify strengths and weaknesses of the implementation strategy and supports and barriers to successful implementation. Rapid qualitative analysis was completed by a team of analysts who transcribed and summarized interviews to identify key domains of interest and emergent themes. Between 2020 and 2023, the SHOUT Texas program expanded to three additional Texas hospital sites, resulting in 3065 hospitalized adult patients starting treatment for OUD. More than 2500 interprofessional clinicians (physicians, nurses, physician assistants, social workers) received SHOUT training regarding inpatient initiation of OUD treatment, with 241 attending at least one hour-long Project ECHO session. Eight key stakeholders at expansion sites were interviewed. Successful components of the SHOUT program included training resources, in-person launches, and collaboration with specialized addiction treatment subject matter experts. Challenges included identifying outpatient follow-up, pharmacy and medication constraints, and nursing education barriers. Interviews also identified lessons learned, advice to other hospitals, and next steps to build capacity. Implementation of the SHOUT Texas model across diverse hospital settings using REP and Project ECHO resulted in significant provider engagement and rapid increase in the number of patients initiating OUD treatment during hospitalization. Lessons learned from this novel approach may be applicable in other states, particularly those that have not expanded Medicaid.